Analysis of Situations in Automated Decision-Making System under On-Line Control of Thermal Power Station Equipment Operation - V. А. Janitsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper gives examples that show how to analyse situations and make a conclusion in an automated decision-making system under on-line control of power station equipment operation. It is revealed that conclusion procedure and algorithm concerning interaction of system separate parts significantly depend on the fact as far as single-meaning conclusions can be obtained on the basis of automatically measured information about an object to be controlled.